Arts Education Within The Mayong Pottery Artisan Families: A Local Art Conservation Strategy (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
This study aims to examine the problem of applying the pattern of traditional arts education in the Mayong ceramic artisan family seen as a strategy in conserving local art. This research used a qualitative-ethnographic approach. The research objectives cover aspects of cultural values of dance, human resources, and the environment and their changes that are systemically related functionally in the art education process in the family sphere. Research data were collected through participatory observation techniques, in-depth interviews, and documentation—validation of data through source triangulation and thick description. Data analysis techniques were carried out in an interactive cycle that moves between the processes of reduction, presentation, and verification of data. The results of the study show the following. First, there are cultural values in the culture of the Mayong ceramic artisan family community, which are oriented to the view of the importance of the obligation to inherit their local arts. Second, human resources, cultural values, and the natural environment show the interrelationships in the formation of art education patterns in the family. Third, as a conservation strategy, the pattern of art education that takes place within the family has succeeded in preserving and developing local ceramic arts. Other local art artisan communities can adopt suggestions that can be put forward in this informal art education pattern in efforts to conserve regional cultural heritage.